THE EFFECT OF OWN CAPITAL AND PEOPLE'S BUSINESS CREDIT ON THE INCOME OF MICRO, SMALL AND MEDIUM ENTERPRISES IN THE SOUTH TAMBUN AREA: KAB. BEKASI - Yusyana Lussardi; Saparuddin Mukhtar; Aditya Pratama (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The purpose of this study was to determine the effect of own capital and people's business credit on the income of MSMEs in the South Tambun area. This study uses primary data with a sample of 325 MSMEs in the South Tambun area calculated using the Taro Yamane formula. Quantitative method was used as the research method. The data analysis used in this research is PLS-SEM using SmartPLS 4.0 software. The results of hypothesis testing show that (1) Own Capital has a positive and significant effect on MSME income; (2) People's Business Credit has a positive and significant effect on MSME income; (3) (3) Own capital has a positive and significant effect on People's Business Credit; (4) Own Capital and People's Business Credit have a positive and significant effect on MSME income. This research is limited because it was only conducted in South Tambun District with variables of Own Capital, People's Business Credit and MSME Income.